Selling Jewish Victims’ Experiences During the Holocaust for Hard Currency: The Case of the Romanian Communists Compensation Claims Collection from 1970 - Mihalcea Eugenia (Eastern European Holocaust Studies)
In the 1970s, the Romanian authorities put together a large collection of compensation claim files of Romanian citizens victims of Nazi persecution between 1939 and 1945. The Romanian Communists’ scope was for a hard-currency settlement with the Federal Republic of Germany. In doing so, the Romanians claimed that the Federal Republic of Germany would pay for persecutions for which the Romanian state had been responsible. The selective denial of the Holocaust was the Communist authorities’ approach to the topic after the end of the Second World War. Especially after 1948, they carefully avoided tackling the issue of country’s own involvement in the persecution of its citizens, externalizing the blame on Nazi Germany. Additionally, in the official narrative the focus was on anti-Fascist resistance and Communists’ martyrdom during the Holocaust and not on Jewish sufferings. By analyzing different claim files part of the larger Romanian collection to be found in the Arolsen Archives I argue that Romanians’ plan of getting Germany’s money–and indirectly recognition of Germany’s responsibility for the Romanian authorities’ wrongdoings during the Holocaust – would have solidified the externalization of blame at international level on the long run.